SOME TYPES OF DOMINATION IN INTUITIONISTIC FUZZY GRAPHS - THAMIZHENDHI, G.; PARVATHI, R. (International Journal of Mathematical Archive, 2018)
In this paper, the concept of edge contraction, fusion of two vertices, pendent dominating set, complementary pendent dominating set, isolate dominating set, doubly isolate dominating set and perfect secure dominating set in IFG have been introduced. Also, some properties of the domination numbers, and with known parameters of are analysed.